PERAN GURU TPQ DALAM MEMBENTUK KARAKTER DISIPLIN SANTRI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN (Studi Kasus di TPQ At-Taqwa Sungegeneng, Sekaran, Lamongan) - Zahira, Tiara; Habibah, Sulhatul; Sun'iyah, Siti Lathifatus (Fakultas Agama Islam, 2024)
TPQ teachers have the responsibility to make their students qualified, both morally and spiritually. The lack of discipline of students in terms of compliance with the set rules, inappropriate behavior, and lack of consistency in getting used to activities, can certainly hinder the smooth running of learning activities. The purpose of this writing is (1) to find out the role of TPQ teachers in shaping the disciplinary character of TPQ At-taqwa students, (2) to find out the efforts made by TPQ teachers in shaping the disciplinary character of TPQ At-taqwa students. In this study, a qualitative descriptive method is used. The data collection techniques used are observation, interviews, and documentation. And the data analysis used is data reduction, presentation of data and drawing conclusions. presentation of data and drawing conclusions. The results of this study show that: 1) the role played by TPQ At-taqwa teachers in shaping the character of student discipline is the first; teachers as role models for students, second; teachers as advisors for students, and third; TPQ teachers foster related to student discipline. 2) The efforts made by TPQ teachers in shaping the disciplinary character of students are TPQ teachers in coaching related to the disciplinary character of students, TPQ teachers supervise and coach students, and TPQ teachers communicate with students' guardians.